2014
DOI: 10.1016/j.visres.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Saccade-target selection of dyslexic children when reading Chinese

Abstract: This study investigates the eye movements of dyslexic children and their age-matched controls when reading Chinese. Dyslexic children exhibited more and longer fixations than age-matched control children, and an increase of word length resulted in a greater increase in the number of fixations and gaze durations for the dyslexic than for the control readers. The report focuses on the finding that there was a significant difference between the two groups in the fixation landing position as a function of word len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Experiment 2 was designed to test whether parafoveal word-boundary information influences saccade generation in sentence reading. Differences in FL imply that saccade generation can make use of information beyond the character level, and thus are in agreement with the flexible eye-guidance model (Pan, Yan, Laubrock, Shu, & Kliegl, 2014;Yan et al, 2010). As compared to Yan and Kliegl (2016), the present results are obtained from a larger set and a more representative sample of materials.…”
Section: Discussionsupporting
confidence: 79%
“…Experiment 2 was designed to test whether parafoveal word-boundary information influences saccade generation in sentence reading. Differences in FL imply that saccade generation can make use of information beyond the character level, and thus are in agreement with the flexible eye-guidance model (Pan, Yan, Laubrock, Shu, & Kliegl, 2014;Yan et al, 2010). As compared to Yan and Kliegl (2016), the present results are obtained from a larger set and a more representative sample of materials.…”
Section: Discussionsupporting
confidence: 79%
“…This motivates us to study the major factors that cause the different effects of space use in Chinese text. We also examine saccade target selection in Chinese reading through spacing conditions because it is still unclear which factors determine where to move the eyes during Chinese reading (Li, Bicknell, Liu, Wei & Rayner, ; Li, Liu & Rayner, , ; P. Liu, Li, Han & Li, ; Y. Liu, Reichle & Li, ; Ma, Li & Pollatsek, ; Pan, Yan, Laubrock, Shu & Kliegl, ; Shu, Zhou, Yan & Kliegl, ; Yan, Kliegl, Richter, Nuthmann & Shu, ; Zang et al, ).…”
Section: List Of Possible Facilitatory and Inhibitory Effects Of Spacsupporting
confidence: 85%
“…Yen, Tsai, Tzeng and Hung (2008) found that Chinese readers were less likely to skip target words when pseudo-word previews, as compared to unrelated word previews, were presented. Pan et al (2014) reported that first of multiple-fixations were characterized by further launch site (i.e., the distance between the last fixation and the beginning of the fixated word) and shorter incoming saccade amplitude as compared to single fixations, suggesting that it is less unlikely for readers to successfully segment parafoveal words when the eyes are distant from them. In the present study, parafoveal word segmentation is tested from a perspective of preview cost effect: as compared to the nonword preview, the unrelated word preview caused more interference to the processing of the target word when the pretarget word is visually complex (and thus preview time is long).…”
Section: Discussionmentioning
confidence: 99%